Sensory characterization of a ready-to-drink beverage based on coconut water (Cocos nucifera L.) (Agroindustria, Sociedad y Ambiente, 2020)
Alcoholic beverages have a consolidated market, with a shallow category such as the "Ready to drink" beverage that has a low alcohol content. Coconut water is a derivative that represents a niche market, for its pleasant moisturizing and sensory qualities it offers. In this sense, it was proposed to sensorially characterize a RTD beverage based on coconut water (Cocos nucifera L.) applying the CATA methodology ("check all that apply"). Carrying out a market study, to select the most accepted flavoring, a CATA test with 30 descriptors was applied to know the characteristics that can improve the drink. The product was prepared with pasteurized coconut water and clarified with unflavored gelatin, extra neutral ethyl alcohol, sugar, flavoring and preservative. The proportion of sugar and alcohol was varied to obtain four different formulations. Fifty consumers were used to measure the acceptability of the beverage with a 9-points structured hedonic scale and to describe the product and ideal drink by the CATA methodology using 14 sensory descriptors. The acceptability of the product evaluated was 6.04 to 6.76 where the highest value was assigned to the beverage with the highest sugar and alcohol content. The ideal drink was described with coconut water flavor, pineapple flavor, pineapple aroma, sweet, corpulent and acidic. It is possible to prepare pleasant coconut water RTD beverage using a proportion of 10° G.L and 3% sugar.
Keywords: Cocos nucifera L.; ethyl alcohol; drinks; Check all that apply; sensory descriptive analysis